Overexpression of metalloproteinase PAPPA accelerates cancer progression and correlates with immune cell infiltration in gastric cancer: insights from bioinformatics and in vitro investigations - Shiya Yu; Shiyao Zheng; Jinwei Qiu; Hongming Lin; Xiaojuan Yu; Huiyan Chen; Junhong Wu; Weihang Wu; Jiong Chen; Yongyuan Chen; Jianwei Chen; Hu Zhao; et al. (Cancer Cell International)
Abstract Background Gastric cancer (GC) is one of the most common malignant tumors in the digestive system. However, the development of its targeted therapies has been slow. Therefore, exploring the mechanisms of malignant behavior of GC is key to developing their treatment methods. Pregnancy-associated plasma protein-A(PAPPA) is thought to play an important role in the occurrence and progression of cancer, yet its significance in the development of GC has not been reported. Methods Bioinformatics analysis elucidated PAPPA's expression in GC and its prognostic significance. The study correlated PAPPA expression with immune infiltration and signaling pathways. Cellular assays, including CCK-8, Western blotting, and flow cytometry, were utilized to examine PAPPA's role in gastric cancer cell apoptosis, migration, and invasion. Results Bioinformatics analysis has demonstrated that the expression of PAPPA is upregulated in GC and correlates with poor prognosis. Correlation and Cox regression analyses have revealed that TNM staging, pathological staging, age, outcome assessment, postoperative tumor residue, and PAPPA expression are prognostic determinants in GC. Further analysis indicates that PAPPA is associated with the infiltration of various immune cells and pathways related to GC. Cellular experiments have shown that PAPPA promotes cell proliferation, and its deficiency can inhibit the proliferation of GC cells, inducing cell cycle arrest at the G1/S phase. Conclusions The findings of this investigation suggest that PAPPA serves as a crucial modulator of GC, underscoring its potential as a GC treatment target.